Predictors of mortality in children with acute kidney injury in intensive care unit - Umi Rakhmawati; Indah K. Murni; Desy Rusmawatiningtyas (Indonesian Pediatric Society, 2019)
Background Acute kidney injury (AKI) can increase the morbidity and mortality in children admitted to the pediatric intensive care unit (PICU). Previous published studies have mostly been conducted in high-income countries. Evaluations of possible predictors of mortality in children with AKI in low- and middle-income countries have been limited, particularly in Indonesia. Objective To assess possible predictors of mortality in children with AKI in the PICU. Methods We conducted a retrospective cohort study at Dr. Sardjito Hospital, Yogyakarta, Indonesia. All children with AKI admitted to PICU for more than 24 hours from 2010 to 2016 were eligible and consecutively recruited into the study. Logistic regression analysis was used to identify independent predictors. Results Of the 152 children with AKI recruited, 119 died. In order to get a P value of <0.25, multivariate analysis is run to degree AKI, ventilator utilization, primary infection disease, MOF and age.Multivariate analysis showed that ventilator use, severe AKI, and infection were independently associated with mortality in children with AKI, with odds ratios (OR) of 19.2 (95%CI 6.2 to 59.7; P<0.001), 8.6 (95%CI 2.7 to 27.6; P<0.001), and 0.2 (95%CI 0.1 to 0.8; P=0.02), respectively. Conclusion The use of mechanical ventilation and the presence of severe AKI are associated with mortality in children with AKI admitted to the PICU. Interestingly, the presence of infection might be a protective factor from mortality in such patients.